COMPOSIÇÃO FLORÍSTICA E FITOSSOCIOLÓGICA DE FLORESTA OMBRÓFILIA MISTA EM ÁREAS SOB MANEJO SILVIPASTORIL E SUCESSÃO SECUNDÁRIA - Mazon, Joelmir Augustinho (2014)
This study aimed to characterize and compare through floristic and phytosociological parameters of the arboreal and regeneration strata differences between the species composition and forest structure in two sample units of high montane Araucaria Forest in different schemes: one in a silvopastoral system with 2 hectares and another on a legal reserve, with 1.8 ha, where spontaneous regeneration was allowed during the last twenty years and which is in the secondary stage of succession, located in the municipality of Turvo-PR. In these fragments were considered for sampling the arboreal strata all individuals with DBH ? 5 cm, and regenerative stratum,the individuals with dbh ? 5 cm, sampled in subplots of three size classes of height (C1: 0.2 m ? 0, 5 m, C2 ? 0.51 ? 1.3 m me and C3:> 1.3 m DBH ? 5), which the floristic parameters, dispersal syndromes, ecological groups, horizontal and vertical structure, Sørensen similarity and Shannon (H`) and Simpson (D) diversity Index were analyzed and compared statistically. Both sample areas showed floristic similarity on the arboreal and regeneration strata, but with less uniformity, density of individuals, richness, diversity and aggregation of species in the arboreal strata. The silvopastoral system area presented 580.5 ind.ha?¹ and 44 species, while in secondary forest area 1,411.7 ind.ha?¹ and 68 species were sampled. The less density and diversity of the silvopastoral system area were reflected in a in the regeneration strata in which, where only 81 individuals were sampled, estimated at 19,094 ind.ha?¹ and 25 species, with a higher percentage of individuals found in the class C1, highlighting the herbaceous-shrubby specie Mollinedia clavigera Tul. In the of secondary forest sample, 433 subjects were measured (46,840 ind.ha?¹), distributed more evenly among the classes of height, composed of 54 species, where Allophylus edulis (A.St.-Hil., Cambess. & A. Juss.) Radlk. stands. In both areas most species belonging to the ecological group of secondary and zoochory, both in the arboreal strata as in natural regeneration. The Extended Importance Value (EIV) pointed as the three most important species and the possibility of staying in the future forest structure: Ilex paraguariensis A. St.-Hil, Araucaria angustifolia (Bertol.) Kuntze and Ocotea porosa (Ness) Barroso in the silvopastoral system sample area, and Ocotea porosa, Matayba elaeagnoides Radlk. and Myrsine umbellata Mart in the secondary forest area sample, revealing the floristic and structural differences resulting from the use and conservation system adopted in each sampling area.